Lingual foregut duplication cysts in the Neonate: Potential role for marsupialization as initial management. (March 2016) - Bray, Haley N; Muelleman, Thomas J; Bhalla, Vidur; Paulson, Lorien M
Abstract: Foregut duplication cysts (FDCs) are a rare clinical entity encountered by otolaryngologists. Imaging can be suggestive of FDCs, but diagnosis is confirmed by pathological analysis. Traditional management has consisted of definitive surgical excision. We describe a case of a neonate born with a ventral tongue FDC which prevented mouth closure and precluded oral intake. Due to excessive potential for morbidity with surgical excision, the cyst was managed primarily by surgical marsupialization. We review the literature, and suggest that marsupialization may be a desirable temporizing measure for oral cavity cysts, offering an initial alternative to complete excision in the neonatal period.